Validation of a quick and simple chromatographic method for simultaneous quantification of sertraline, escitalopram, risperidone and paliperidone levels in the human plasma - Jeremić, Aleksandra; Milosavljević, Filip; Vladimirov, Sandra; Batinić, Bojan; Marković, Bojan; Jukić, Marin (Archives of Pharmacy, 2021)
Simultaneous quantification of multiple psychiatric drugs is important for the therapeutic drug monitoring of psychiatric patients. In addition, it would be highly advantageous if the method could be simple, straightforward, and not time-consuming. A 200 µl plasma sample was deproteinized, drugs were separated by a ZORBAX Eclipse XDB-Phenyl column with the mobile phase composed of acetonitrile and 0.1 % formic acid in water (60:40, v/v), and recorded in the MRM mode by using a positive electrospray source with tandem mass spectrometry detection. The dynamic range was 2–256 ng/ml for all the analyzed drugs, except escitalopram (8-256 ng/ml). Quality control samples were prepared in quintuplicates in three relevant concentrations for each drug. Coefficients of determination (R2) were higher than 0.99, while the relative difference between nominal and measured concentrations (RE) and CV were lower than 15% for all targets. High performance liquid chromatography coupled with the mass detector (HPLC-MS/MS) method for simultaneous determination of sertraline, escitalopram, risperidone and paliperidone in human plasma was validated with respect to selectivity, linearity, accuracy, precision, matrix effect and stability. This method has significant advantages in terms of low sample volume (200 µl), short preparation time (3 hours) and short runtime per sample (4 minutes).